Implementation of Dasa Darma Pramuka Values in the Formation of Student Discipline at SMPN 6 Purwakarta - Suharyanto Soro; Nana Herdiana Abdul Rahman; Ahmad Muammar ZA; Ridha Anggara (Global Education Journal, 2026)
This study aims to find and analyze the implementation of Dasa Darma Pramuka values in extracurricular activities as well as positive contributions in the formation of student discipline character. This research uses a case study approach. Data were collected through participatory observation methods, in-depth interviews, documentation studies. The data analysis technique was carried out in a descriptive-thematic manner to identify the pattern of value implementation, internalization process, the role of coaches, as well as supporting and inhibiting factors in the implementation of activities. The results of the study show that (1) the values of Dasa Darma Pramuka are implemented systematically through habituation, example, and structured scouting activities, such as marching, apples, squad work, and assignments; (2) The process of internalizing grades takes place in a sustainable manner and has a positive impact on improving student discipline as reflected in punctuality, compliance with rules, responsibility, and behavioral regularity in daily school life. The conclusion of this study is that the implementation of the dasa darma scout value can shape the discipline of SMPN 6 Purwakarta students.